Descriptive study of cattle and dog rabies cases in the Sheki-Zagatala region of Azerbaijan (2015–2016): Knowledge, attitudes, and practices of people towards rabies - Eldar Hasanov (Public Library of Science (PLoS), 2021)
Every year, rabies causes great damage to human health and the economy of countries around the world. This neurotropic and zoonotic viral disease is endemic to Azerbaijan. This study describes cattle and dog rabies cases identified between 2015 and 2016. In addition, a questionnaire was administered to 100 respondents comprised of case owners, and non-case animal owners, to assess knowledge, attitudes, and practices within this population. The study demonstrates a general lack of knowledge of rabies in the participating communities. The majority of respondents were familiar with rabies and understood that animal bites are a source of transmission. However, many respondents did not know that rabies is preventable and admitted not knowing additional routes of transmission. In addition, there was less perceived risk with contact with animal saliva. Despite free vaccinations in Azerbaijan, only 27 out of 45 dogs in this study were vaccinated. Although educational programming and preventive vaccination of dogs has been implemented, and significant progress has been made in the sphere of epidemiological surveillance and prevention, rabies cases remain problematic in the Sheki-Zagatala region. Regular educational programs for communities, strengthening of the existing vaccination programs, and a comprehensive epidemiological case-control study to identify the disease risk factors could help reduce the burden of rabies in Azerbaijan.